Urgent ultrasonographic diagnostics in acute nontraumatic abdominal conditions (emergency abdominal ultrasound) - Vasin Dragan; Pavlović Aleksandar; Stojadinović Milica; Mijović Ksenija; Maričić Bojana; Jovandić Biljana; Mašulović Dragan (Serbian Journal of Anesthesia and Intensive Therapy, 2021)
Ultrasound is an essential and often initial visualization diagnostic procedure in all algorithms for urgent care of acute abdominal conditions. Ultrasound is a fast, accessible, non-invasive diagnostic examination method that does not involve ionizing radiation and can be repeated. It is vital in detecting free fluid in the abdominal cavity, acute pathological conditions of parenchymal and hollow organs, and assessing volemic status. Ultrasound efficiently and accurately diagnoses acute pathological conditions of the hepatobiliary and urogenital system. It certainly makes a significant contribution to the definitive diagnosis of pathological conditions of the gastrointestinal and vascular systems and can help detect pneumoperitoneum as an indication for urgent surgical treatment.